Strategi Rebranding Daerah Oleh Pemerintah Kabupaten Sidoarjo Melalui Tagline #Disidoarjoaja - Fitria Widiyani Roosinda; Ariyan Alfraita; Andini Astu Prameswari (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
In the current era of competition, a region is not only required to deliver optimal public services but also to build a positive image and strengthen its regional identity. This study aims to examine the regional rebranding strategy through the #DiSidoarjoAja tagline implemented by the Sidoarjo Regency Government to support integrated regional promotion. The research employs a qualitative descriptive method with data collected through in-depth interviews, observation, and documentation. The analysis is based on Simon Anholt’s Hexagon of Competitive Identity theory, which consists of six dimensions: tourism, brand, policy, culture, people, and investment. The findings indicate that the government has optimized the development of tourism potential across various areas, reinforced regional uniqueness and identity through branding, and issued policies that encourage regional progress. In addition, community participation plays a significant role as a representation of Sidoarjo’s image, while investment flows show potential to further enhance the region’s competitiveness in the future. The study concludes that regional rebranding through the #DiSidoarjoAja tagline primarily emphasizes the tourism dimension as a key strength of regional identity, whereas the investment dimension has not yet been optimally developed, and other dimensions remain in a stage of ongoing and sustainable development.